PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS V SDN 029 TELUK ERONG KECAMATAN RENGAT - Efniwaty '; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of this research is based on the fact that happened in class V SDN 029 Teluk Erong Kecamatan Rengat, which indicates a low reading skills of students. The problem of this research is "Does the application of direct instructional model can improve students 'reading comprehension Class V SDN 029 Teluk Erong Kecamatan Rengat?" The purpose of this research is to improve students' reading comprehension Class V SDN 029 Teluk Erong Kecamatan Rengat by applying the model direct learning. This study took place in class V SDN 029 Teluk Erong Kecamatan Rengat and held on 5 April until 22 April 2016 with a number of subjects as many as 12 people consisting of 2 women and 10 men. This research is a classroom action research conducted in two cycles. Based on the results obtained by the percentage of individuals and classical completeness by applying direct learning model, before the action amounted to 16.7% and the students who did not complete 83.3%, in the first cycle increased by 66.7% and that is not finished at 33.7%. Then on the second cycle increased by 91.7%, while 9.3% did not complete. In the second cycle the average student learning outcomes 60% and increased to 72.5% in the first cycle, the difference in the increase of the value of the previous test was 20.8%. In the second cycle the average results of tests students' return increased to 82.5% margin improvement that occurred from the first cycle to the second cycle is sebesar13,8%. So the increase in students' test results is by 34.6% overall. From the results of these actions can be summed application of direct learning model can improve students' reading comprehension class V SDN 029 Teluk Erong Kecamatan Rengat.Keywords: Direct Learning Model, Capability Reading, Comprehension